Implementasi Nilai-nilai Spiritual dalam Pendidkan (Studi Kasus MTs. Barakatul Walidain Rarangan Pijot Lombok Timur) - Nasri, Nasri (Lembaga Yasin AlSys, 2022)
Value is something that can be used as a target to achieve a goal that becomes a noble trait consisting of two or more components that influence each other. Value in Islam is the result of qur'ani education developed as prophetic ethics used as a substance in Islamic education. Islamic spiritual values are immaterial in the form of inner beliefs, which are sourced from the values contained in the Qur'an and as-Sunnah. Islamic spiritual values have a transcendental intelligence relationship, located in the inner heart which is considered to have sacred, holy and great power.